The peculiarities of growing a cucumber in the second turnover - Ovechko, K. O. (ТДАТУ, 2019)
Therefore, for a hybrid grown in the second turnover, it is essential that it will be highly resistant to viral diseases. Also the property to bear fruit during cold periods is needed. When the air temperature drops to 10-12°C at night, the plants must retain the ability to regenerate and form fruits. Harvesting of cucumbers in a non-heating greenhouse is usually carried out before the first frost, in heated sheltered soil it can be grown until December.
Keywords: growing a cucumber; the sheltered soil; greenhouses